STUDYING THE DYNAMIC CHARACTERISTICS TO LENGTHEN THE OPERATING LIFE FOR A DIESEL ENGINE USING FREQUENCY RESPONSE FUNCTION (FRF) MEASUREMENT - Subekti Subekti (SINERGI, 2018)
This research was conducted on Diesel engine single cylinder which aims to study the dynamic characteristics of Diesel engine type HATZ 1D 80 made in Germany. The test was performed by measuring the Frequency Response Function (FRF). In this study, the vibration response was measured at three points: point A which was situated below the engine shaft and in line with the stinger. Point A indicated the FRF point. Point B was located in the valve train component, while point C was situated above the cap of the valve train component. The range of frequencies applied was 0 - 3200 Hz, 3200 - 6400 Hz, 6400 - 9600 Hz, and 9600 - 11200 Hz. This research indicates that the natural frequencies arose because of the global vibration mode. The global vibration mode occurred at natural frequencies of 3118, 4805, 4821, 5021, 7129, 8601, and 11107 Hz. While other natural frequencies were associated with the local vibration mode because it appears only at one point of measurement.